STORYTELLING AS CONTENT MARKETING STRATEGY FOR NNYL STUDIO (The Indonesian Journal of Business Administration, 2019)
Business industry have had enough with faster, stronger, cheaper etc. Many of SME are tired of having competition about valueless things that seems like an endless battle. Stories on the other hand, delivered intangible value and human spirit; it has powerful impact into customer engagement and sustainability of company.Nnyl studio is creative studio that work on customize sewn stuff. Handmade stuffed toy company’s signature products. The value is committed to make people realize their need to express their emotion and originality through personalized goods. In the first year, Nnyl studio did nothing about marketing plan; so the growth is too slow. Using storytelling method is necessary to meet the right market and also create new market.In the first year, Nnyl studio's sales activities has been relied on word-of-Mouth. Existing customers mapping were analyzed from many perspective to find the red thread of customer’s tendency. Then deep interview also held to get insights from ideal customers. This research using several method and tools that stand for value of Nnyl Studio itself as service-design based company.This study used qualitative approach after examined quantitative data. The result of the study indicates that Storytelling is fit for Nnyl Studio target audiences. The implementation plan of this research are graph of storytelling strategic plan and the stages of storytelling for Nnyl Studio.Keywords : Brand value, Content marketing, Customer engagement, Storytelling.